The Association Between Peptic Ulcer Disease and Ischemic Stroke: A Population-Based Longitudinal Study. Issue 22 (May 2016) - Cheng, Tain-Junn; Guo, How-Ran; Chang, Chia-Yu; Weng, Shih-Feng; Li, Pi-I; Wang, Jhi-Joung; Wu, Wen-Shiann
Abstract : Abstract: Stroke is a common cause of death worldwide, but about 30% of ischemic stroke (IS) patients have no identifiable contributing risk factors. Because peptic ulcer disease (PUD) and vascular events share some common risk factors, we conducted a population-based study to evaluate the association between PUD and IS. We followed up a representative sample of 1 million residents of Taiwan using the National Health Insurance Research Database from 1997 to 2011. We defined patients who received medications for PUD and had related diagnosis codes as the PUD group, and a reference group matched by age and sex was sampled from those who did not have PUD. We also collected data on medical history and monthly income. The events of IS occurred after enrollment were compared between the 2 groups. The data were analyzed using Cox proportional hazard models at the 2-tailed significant level of 0.05. The PUD group had higher income and prevalence of hypertension, diabetes mellitus (DM), heart disease, and hyperlipidemia. They also had a higher risk of developing IS with an adjusted hazard ratio of 1.31 (95% confidence interval: 1.20–1.41). Other independent risk factors included male sex, older age, lower income, and co-morbidity of hypertension, diabetes mellitus (DM), and heart disease. PUD is a risk factor for IS, independent of conventional risk factors such as male sex, older age, lower income, and co-morbidity of hypertension, DM, and heart disease. Prevention strategies taking into account PUD should be developed and evaluated.